Machine vision and planning applied on assembby line of multiple products - Lemos, Marilza Antunes de [UNEP]; Liberado, Eduardo; Botura Júnior, Galdenoro [UNESP]; Marques, Marcio Alexandre; Rosa, Luiz Carlos (My University, 2012)
This article describes the use of Artificial Intelligence (IA) techniques applied in cells of a manufacturing system. Machine Vision was used to identify pieces and their positions of two different products to be assembled in the same productive line. This information is given as input for an IA planner embedded in the manufacturing system. Therefore, initial and final states are sent automatically to the planner capable to generate assembly plans for a robotic cell, in real time.